Implementasi dan Digitalisasi Sistem Administrasi Desa di Kantor Desa Kedungcino Kecamatan Jepara - Asep Ferdinan; Tri Listyorini; Endang Supriyati (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2023)
Kedungcino Village is a village located in Jepara District, Jepara Regency. Kedungcino Village is one of the government agencies engaged in community service, but this community service is still not optimal and has many obstacles. One of the obstacles is the availability of village administration information that can be easily accessed by the community and making letters in the village takes quite a long time because it is still manual. People are even more lazy to go to the village office. In the era of digitalization, the Kedungcino Village government really needs a website-based information system application that contains information about the village and administrative services for submitting letters. So that the community will be greatly assisted and services from the Kedungcino Village Government can be carried out optimally. Based on the description of the problem, researchers will conduct research with the title "Implementation and Digitalization of the Village Administration System in the Kedungcino Village Office, Jepara District". This system was built using the waterfall model development method and created using the Hypertext Preprocessor (PHP) programming language with the Laravel Framework, MYSQL database and XAMPP as the system's local server. The purpose of this research is to make it easier for the community to receive the latest information, to make it easier for the community to administer the submission of letters and to increase the efficiency of services from the Kedungcino Village Government.